Clinical Outcomes and Complications of Intramedullary Proximal Phalanx Fixation - Emma Roccaforte; Justin Choy; Winston Scambler; Matthew Kannenberg; William F. Pientka (HAND, 2026)
Background: Proximal phalanx fractures are common hand injuries that can result in significant functional impairment if inadequately treated. While multiple fixation strategies exist, the optimal approach remains debated. Intramedullary headless screw fixation has gained interest due to its minimally invasive nature and ability to allow early mobilization. This study evaluates clinical, radiographic, and functional outcomes following fixation with a single intramedullary device. Methods: A retrospective review was performed of patients undergoing proximal phalanx fracture fixation with the ExsoMed InFrame nail at a single center. Data collected included demographics, operative time, alignment, time to union, return to activity, range of motion, therapy participation, follow-up duration, and complications. Results: Fifty-one patients with a total of 57 fractures were included, with a mean age of 44.3 years (range, 17-76). Fractures involved 1 thumb, 15 index, 8 middle, 15 ring, and 18 small fingers. Mean operative time was 71.7 minutes, and final coronal alignment averaged 3.56°. Radiographic union occurred at a mean of 5.0 weeks, and unrestricted activity was achieved at 8.2 weeks. At a mean follow-up of 10.7 weeks, active and passive total arc of motion averaged 202.4° and 213.9°, respectively. Seventeen patients participated in hand therapy (mean 5.4 visits). Complications included stiffness in 24 digits, tenolysis in 3 digits, hardware removal in 1 digit, and periprosthetic fracture in 1 digit. Conclusions: Intramedullary fixation with the ExsoMed InFrame system provides reliable union and favorable early functional outcomes. However, the high rate of postoperative stiffness highlights the need for structured rehabilitation and further comparative study.